2020
DOI: 10.1017/s1743923x20000410
|View full text |Cite
|
Sign up to set email alerts
|

Local Responses to a Global Pandemic: Women Mayors Lead the Way

Abstract: Even before the novel coronavirus, COVID-19, was declared a pandemic, prominent women mayors in the United States enacted proactive and innovative policies to prevent local outbreaks and soften the social and economic repercussions. Several Black women mayors, in particular, have led the way in local pandemic response efforts. This article identifies four major features of these and other women mayors’ early responses. First, women mayors demonstrated proactive leadership even when faced with pushback. Second,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Our analysis demonstrates how certain policy interventions related to COVID-19 exacerbated the preexisting asymmetrical division of household labor between men and women (Dinh, Strazdins, and Welsh 2017 ; Orloff 2002 ). This research contributes to a growing body of evidence on the gendered implications of policy measures related to COVID-19 (Funk 2020 ; Shay 2020 ). In particular, we provide empirical validation of claims that gender disparities in households with children have been amplified as a result of the pandemic.…”
mentioning
confidence: 92%
“…Our analysis demonstrates how certain policy interventions related to COVID-19 exacerbated the preexisting asymmetrical division of household labor between men and women (Dinh, Strazdins, and Welsh 2017 ; Orloff 2002 ). This research contributes to a growing body of evidence on the gendered implications of policy measures related to COVID-19 (Funk 2020 ; Shay 2020 ). In particular, we provide empirical validation of claims that gender disparities in households with children have been amplified as a result of the pandemic.…”
mentioning
confidence: 92%
“…Although the mainstreaming culture of disaster and emergency management leadership has been male-dominated (Wilson 1999 ), an increasing number of female leaders has been shifting this culture towards a more gender-equal perspective (Drolet et al 2015 ). Female political leaders and medical officers world-wide have demonstrated their strong leadership in response to the COVID-19 pandemic (Funk 2020 ). Cvetkovic et al ( 2018 ) indicated that women’s traditional and natural caring characteristics enable them, when disaster hits, to take up leadership roles in support of their families’ safety, health, and well-being, and in helping their neighbors and other people affected by the disaster.…”
Section: Female University/college Students and Disaster-specific Leadershipmentioning
confidence: 99%
“…Woman leadership has gradually been transforming this landscape by focusing on overall disaster mitigation [24]. In particular, compared with the man-only leadership, Funk [25] indicates that women mayors in the U.S. released disaster mitigation policies to prevent local risks and reduce negative social and economic consequences prior to the declaration of public emergency of COVID-19. Furthermore, the increasing number of women leaders not only benefit citizens affected by disaster, but also influence their nation's bilateral foreign aid to other international communities regarding disaster risk reduction [26].…”
Section: Women's Leadership In Political and Professional Realmsmentioning
confidence: 99%
“…The gender leadership gap is outstanding in the man-dominated political and professional fields [49]. Amid the unprecedented global pandemic of COVID-19, emerging research focusing on international women leaders has predominantly highlighted that their decision-making capacity, including responding actions and communication approaches, have been better than their men counterparts [25,37,38]. The Canadian dual-gendered leadership provides a valuable opportunity to redress gender disparities in scientific-political communication by investigating women's collaborative performance with their men political counterparts to strengthen public health communication.…”
Section: Gender-inclusive Scientific-political Communication During the Covid-19 Pandemicmentioning
confidence: 99%